The Russian cold : histories of ice, frost, and snow - Herzberg, Julia; Renner, Andreas, 1964-; Shirle, I. (Ingrid) (Environment in history ;, 2021)
"Cold has long been a fixture of Russian identity both within and beyond the borders of Russia and the Soviet Union, even as the ongoing effects of climate change complicate its meaning and cultural salience. The Russian Cold assembles fascinating new contributions from a variety of scholarly traditions, offering new perspectives on how to understand this mainstay of Russian culture and history. In chapters encompassing such diverse topics as polar exploration, the Eastern Front in World War II, and the iconography of hockey, it explores the multiplicity and ambiguity of "cold" in the Russian context and demonstrates the value of environmental-historical research for enriching national and imperial histories"--